The ECB and the bond market - Favero, Carlo; Giavazzi, Francesco; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium: European Comission: Directorate-General for Economic and Financial Affairs, 2008)
Despite the fact that the correlation between policy rates in the U.S. and in the euro area has been low-at least over the past three decades-long term interest rates in the two regions have been highly correlated. More recently (since the early 1990s) their levels have also converged. Decomposing long-rates in their underlying factors-real rates (plus an inflation risk premium), term premia, expected monetary policy and expected inflation-we find that this convergence reflects more similar economic structures in the U.S. and in the euro area, rather than a change in the distribution of shocks that hit the two regions. As far as the response to shocks is concerned, since the start of EMU Euro area long rates have become more responsive to local non-monetary shocks: in the long run, however, they converge to the same level of U.S. long rates because expected inflation and expected monetary policy also converge to similar levels. Policy rates in the euro area have also become more responsive to local non-monetary shocks. Finally, since the start of EMU, a monetary tightening by the ECB raises long rates, contrary to what used to happen in the 1990s when the Bundesbank was running monetary policy. Interestingly long rates in the Euro area fall following a monetary tightening in the U.S.
Economic Papers